Cuidados Bucais em Pacientes Oncopediátricos durante a Pandemia de Covid-19: o Que Está Mudando? - de Araújo Ferreira Muniz, Isis; Gomes dos Santos, Fabio; Gondim Valença, Ana Maria; Alves de Sousa, Simone; Batista Medeiros-Serpa, Eliane; Ferreti Bonan, Paulo Rogério (Revista Brasileira de Cancerologia, 2020)
During the last weeks, we are facing a global pandemic which affects the general population and health care system. Observing COVID-19 care, hospitals and health care services are focusing their attention on COVID-19 combat. Considering this emergency, structural and logistic impacts over health services are perceived evidently and conventional routines of multiprofessional teams are being dramatically changed.